Food preferences, dieting behaviors, and body image perceptions of elite figure skaters - Jonnalagadda, S. S.; Ziegler, P. J.; Nelson, J. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
The objectives of this study were to determine food preferences, body image perceptions, dieting behaviors, and nutrient intakes of elite male and female figure skaters. Male (n = 23) and female (n = 26) figure skaters completed a food preference checklist, a questionnaire examining their demographics, dieting behaviors and body image perceptions, and 3-d food records. Male skaters had a higher preference (score ³ 6) for grains, fruit, meat, dairy, fats, and sweets. Female skaters had higher preference for grains and fruits. Of the female skaters, 30% considered themselves overweight and indicated a preference for a thinner body contour. Both male and female skaters expressed a preference for leaner body contours for members of the opposite gender. Total energy intake, total fat (females) and dietary fiber were below the dietary recommendations. Vitamin E, vitamin D, folate (females), pantothenic acid (females), calcium (females), magnesium, potassium, and phosphorus (females) were less than two-thirds of the dietary recommendations. Macronutrient intake of male skaters was associated with preferences for the grain group, although no association was observed among female skaters. Results suggest that these behaviors and attitudes need to be assessed and addressed among figure skaters, given their impact on dietary intakes and overall well-being